Heparanase-2 protein and peptides have a protective effect on experimental glomerulonephritis and diabetic nephropathy - Buijsers, Baranca; Garsen, Marjolein; de Graaf, Mark; Bakker-van Bebber, Marinka; Guo, Chunming; Li, Xue; van der Vlag, Johan (Frontiers in Pharmacology, 2023)
The endothelial glycocalyx degrading enzyme heparanase-1 (HPSE1) is a major contributor to kidney diseases, such as glomerulonephritis and diabetic nephropathy. Therefore, inhibition of HPSE1 could be an interesting therapeutic strategy to treat glomerular diseases. A possible HPSE1 inhibitor is heparanase-2 (HPSE2) because HPSE2 is a structural homolog of HPSE1 without enzymatic activity. The importance of HPSE2 has been recently demonstrated in HPSE2-deficient mice, since these mice developed albuminuria and died within a few months after birth. We postulate that inhibition of HPSE1 activity by HPSE2 is a promising therapeutic strategy to target albuminuria and resulting renal failure. First, we evaluated the regulation of HPSE2 expression under inflammatory and diabetic conditions by qPCR and ELISA. HPSE2 expression was down-regulated in anti-GBM and LPS-induced glomerulonephritis, streptozotocin-induced diabetic nephropathy, and adriamycin nephropathy, whereas this effect on HPSE2 expression was absent with HPSE1 inhibition and in HPSE1-deficient mice. Second, we assessed the therapeutic potential of HPSE2 protein and 30 different HPSE2 peptides in both experimental glomerulonephritis and diabetic nephropathy. Both HPSE2 protein and a mixture of the three most potent HPSE1 inhibitory HPSE2 peptides could prevent LPS and streptozotocin induced kidney injury. Taken together, our data suggest a protective effect of HPSE2 in (experimental) glomerular diseases and support the therapeutic potential of HPSE2 as HPSE1 inhibitor in glomerular diseases.